Kajian Tata Rias Pengantin Tradisional Suku Sasak di Selong Kabupaten Lombok Timur - Viona Octaviani; Biyan Yesi Wilujeng; Dewi Lutfiati; Dindy Sinta Megasari (Journal of Beauty and Cosmetology (JBC), 2025)
The traditional bridal makeup of the Sasak tribe in Selong, East Lombok, faces challenges due to the shift towards modern styles, threatening its preservation. This study aims to examine the form and meaning of traditional bridal makeup, hair styling, attire, and accessories, as well as to describe the traditional wedding ceremony in 2024. A qualitative descriptive approach was used, employing interviews, observations, and documentation, with data validation through expert triangulation. The findings indicate that traditional bridal makeup for women includes yellowish foundation, vibrant eye and lip colors symbolizing majesty and bravery. Hair styling reflects status and cultural values, such as kepang siak and pangkak kedebong malang. Hair accessories include onggar-onggar (loyalty) and kembang kemiter (cheerfulness). Women's attire consists of baju Ludru (modesty) and songket fabric (life), with accessories like giwang and kalong ringgit symbolizing fertility and unity. The groom wears kelambi pegon (masculinity) and sapu’ or udeng (steadfastness). The wedding processions include Semitra (relationship initiation), Merariq (proposal), Selabar (announcement), Sorong-Serah (handover), Ijab Kabul (ceremony), Nyongkolan (reception), and Bales Lampaq (social gathering).Keywords: bridal makeup, selong, wedding ceremony process.